Take up and use of subsidised public transport: evidence from the English Longitudinal Study of Ageing - Laverty,AA; Millett,C; Webb,E (Journal of Transport and Health, 2018)
BackgroundSince 2006 England has had a bus pass scheme which provides free bus travel for older people. The scheme is universal but there are questions over whether take up is equitable.MethodsData come from waves 6 and 7 of the English Longitudinal Study of Ageing collected in 2012 and 2014. Logistic regression assessed factors associated with take up of a free bus pass by 2014 among eligible people without a pass in 2012, and associations of this with public transport use in 2014.ResultsOf those eligible for a free bus pass in 2012, 16.1% did not have one. 18.8% of these people had taken up a bus pass by 2014. Take up was equitable according to wealth and other individual characteristics but was more common among people retiring from paid work (AOR 2.33, p = 0.025), and moving house (AOR 2.76, p = 0.014). People who took up a free bus pass were more likely to use public transport in 2014 (AOR 3.23, p < 0.001).DiscussionTake up of the free bus pass is equitable across groups, and is strongly linked to public transport use among older people.